Urinary miR-185-5p is a biomarker of renal tubulointerstitial fibrosis in IgA nephropathy - Duan, Zhi-Yu; Bu, Ru; Liang, Shuang; Chen, Xi-Zhao; Zhang, Chun; Zhang, Qiu-Yue; Li, Ji-Jun; Chen, Xiang-Mei; Cai, Guang-Yan (Frontiers in Immunology, 2024)
Background: For IgA nephropathy (IgAN), tubular atrophy/interstitial fibrosis is the most important prognostic pathological indicator in the mesangial and endocapillary hypercellularity, segmental sclerosis, interstitial fibrosis/tubular atrophy, and presence of crescents (MEST-C) score. The identification of non-invasive biomarkers for tubular atrophy/interstitial fibrosis would aid clinical monitoring of IgAN progression and improve patient prognosis. Methods: The study included 188 patients with primary IgAN in separate confirmation and validation cohorts. The associations of miR-92a-3p, miR-425-5p, and miR-185-5p with renal histopathological lesions and prognosis were explored using Spearman correlation analysis and Kaplan-Meier survival curves. Bioinformatics analysis and dual luciferase experiments were used to identify hub genes for miR-185-5p. The fibrotic phenotypes of tubular epithelial cells were evaluated in vivo and in HK-2 cells. Results: miRNA sequencing and cohort validation revealed that the expression levels of miR-92a-3p, miR-425-5p, and miR-185-5p in urine were significantly increased among patients with IgAN; these levels could predict the extent of tubular atrophy/interstitial fibrosis in such patients. The combination of the three biomarkers resulted in an area under the receiver operating characteristic curve of 0.742. The renal prognosis was significantly worse in the miR-185-5p high expression group than in the low expression group (P=0.003). Renal tissue in situ hybridization, bioinformatics analysis, and dual luciferase experiments confirmed that miR-185-5p affects prognosis in patients with IgAN mainly by influencing expression of the target gene tight junction protein 1 (TJP1) in renal tubular epithelial cells. In vitro experiment revealed that an miR-185-5p mimic could reduce TJP1 expression in HK-2 cells, while increasing the levels of α-smooth muscle actin, fibronectin, collagen I, and collagen III; these changes promoted the transformation of renal tubular epithelial cells to a fibrotic phenotype. An miR-185-5p inhibitor can reverse the fibrotic phenotype in renal tubular epithelial cells. In a unilateral ureteral obstruction model, the inhibition of miR-185-5p expression alleviated tubular atrophy/interstitial fibrosis. Conclusion: Urinary miR-185-5p, a non-invasive biomarker of tubular atrophy/interstitial fibrosis in IgAN, may promote the transformation of renal tubular epithelial cells to a fibrotic phenotype via TJP1.